Loor Ortiz,Jeniffer Libany(2023)IMPORTANCIA DE LOS NUTRIENTES PRIMARIOS EN EL DESARROLLO DE PLÁNTULAS DE BANANO CULTIVAR WILLIAMS A NIVEL DE VIVERO.Quevedo.UTEQ.74p. - Loor Ortiz, Jeniffer Libany (2023)
Banana is one of the most important fruits in many countries due to the economic profitability it generates. Banana plantations demand great absorption of mineral nutrients available in the soil, especially nitrogen, phosphorus and potassium. Therefore, the objective of this research was to define the importance of primary nutrients (NPK) in the development of banana seedlings cultivar Williams at the nursery level. The study was carried out at the "La María" University Campus, of the Quevedo State Technical University, located at km 7 of the Quevedo - El Empalme road, Province of Los Ríos. For this trial, a completely randomized design consisting of five treatments and four observations was used: T1 without fertilizer, T2 with complete NPK fertilizer, T3 with PK fertilizer, T4 with NK fertilizer and T5 with NP fertilizer, adding 6 g/plant of edaphic fertilizer in each treatment, evaluating the height, diameter, fresh and dry biomass, number of leaves of banana seedlings. It was observed that, with the addition of nitrogen, potassium (NK) it is possible to obtain a greater height and diameter of the plant with 27.63 and 2.69 cm/plant, respectively. While, with the addition of nitrogen, phosphorous, potassium (NPK) banana seedlings need fewer days to emit a leaf 7.48 days/leaves, respectively. Therefore, the primary nutrients are important in the multiplication of seedlings at the nursery level, managing to obtain banana plants of the Williams variety with the height and diameter required for establishment in the field.